Influence of Positive Thinking Ideology on Physician Representations of Cancer - Luis Felipe Higuita-Gutiérrez; Diego Alejandro Estrada-Mesa; Walter Alfredo Salas-Zapata; Jaiberth Antonio Cardona-Arias (Behavioral Sciences, 2023)
To understand the influence of positive thinking ideology on cancer representations among physicians in the city of Medellín. Methods: This qualitative study was conducted on the basis of the theoretical and methodological elements of Corbin and Strauss’s grounded theory. Fourteen physicians were included and selected according to the criteria of maximum variation for education, years of study, and personal and family history of cancer. The information was collected through semi-structured interviews and analyzed with open, axial, and selective coding. Results: the ideology of positive thinking has managed to permeate the medical discourse and the representations that they form about the etiology and treatment of cancer. Physicians place the mind, emotions, attitude, and positive thinking as determinants of the origin of the disease and the response to therapy. To argue this link, they use two strategies: (i) a sophisticated and specialized discourse that involves relationships among thoughts, genetics, the neurological, immune and endocrine system and (ii) a mystical and less rational discourse that emphasizes the omnipotence of the mind and thoughts. In no case was the idea of positive thinking rejected or in disagreement with this style of thinking expressed. Conclusion: The fact of linking the disease with mental factors refers to the mind–body dualism and generates a responsibility of the patients on the etiology and therapeutics of the disease, as well as an erasure of the social and political determinants of cancer. The technical discourse and the symbolic capital of physicians offer scientific legitimacy to these ideas and can become performative for patients.